2019
DOI: 10.1002/wsb.947
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three methods to evaluate otter latrine activity

Abstract: We compared methods commonly used in the field of river otter (Lontra canadensis) ecology to estimate visitation rates. We evaluated visitation rates estimated from 2 survey protocols based on video detection-individual visitation rate (IVR) and recording visitation rate (RVR)-and one indirect method based on scat detection-scat visitation rate (SVR). From August 2011 through August 2012, overall scat detection and cumulative video data from 403 camera-days in 2 latrine sites (River and Pond, at a study site a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…However, other authors have found high correlation between spraint marking intensity and otter habitat use using camera‐trapping (e.g. Guter et al ; Rivera et al ). Furthermore, molecular genetic research has found a positive correlation between the relative otter spraint density and the number of otter genotypes in the area (Lanszki et al ).…”
Section: Discussionmentioning
confidence: 91%
“…However, other authors have found high correlation between spraint marking intensity and otter habitat use using camera‐trapping (e.g. Guter et al ; Rivera et al ). Furthermore, molecular genetic research has found a positive correlation between the relative otter spraint density and the number of otter genotypes in the area (Lanszki et al ).…”
Section: Discussionmentioning
confidence: 91%
“…During 2018, we conducted non-invasive fecal DNA sampling of otter scats at active latrines located along 259 km of the URG dendritic network using a capture-recapture study design (Figure 3; Brzeski et al, 2013;Mowry et al, 2011). To maximize detection rates, we conducted sampling during February-April, which was within the typical river otter breeding season when latrine visitation and defecation rates are highest (Mowry et al, 2011;Rivera et al, 2019).…”
Section: Genetic Samplingmentioning
confidence: 99%
“…Yet, the intrinsic ecological characteristics of many wildlife species often present considerable difficulty in monitoring their populations. One such example is lutrinids, including North American river otters (Lontra canadensis; Figure 1), which are semiaquatic carnivores with strongly territorial but semi-social behavior that display high site fidelity over surprisingly large areas relative to their body size (Hung & Law, 2016;Larivière & Walton, 1998;Rivera et al, 2019;Stevens & Serfass, 2008). Their expansive territories and movement patterns are primarily structured by the hydrographical systems that they inhabit, such as rivers and coastal shorelines, which represent hierarchical dendritic networks comprised of multiple branches of suitable habitats (Brown & Swan, 2010;Campbell Grant et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otters are secretive, mostly nocturnal living animals, but deposit scats (so-called otter spraints) at conspicuous sites along the watercourse (Reuther et al 2000;Kruuk 2006). Hence, scat count surveys have become a commonly used monitoring approach to ascertain otter distribution range (Reuther et al 2000), habitat selection (Mason and MacDonald 1987;Ottino and Giller 2004;Romanowski et al 2013), activity (Guter et al 2008;Day et al 2016;Rivera et al 2019) and relative abundance (Jefferies 1986;Mason and Macdonald 1987;Strachan and Jefferies 1996). While scat surveys are an approved method to assess otter distribution (the so-called standard survey method according to Reuther et al 2000), doubts and criticism have been raised on the validity and accuracy of this technique for conservation assessments (Reid et al 2013) and to assess population density, as well as habitat utilisation (Kruuk et al 1986;Kruuk and Conroy 1987).…”
Section: Introductionmentioning
confidence: 99%